Optimization of titanium dioxide (TiO2) thin film using dip coating technique for oxygen gas sensor - Bakri, Anis Suhaili (2017)
Titanium dioxide (TiO2) thin film gas sensors have been widely used and investigated in the detection of target gases. However, to obtain anatase phase for oxygen gas sensor with low and short annealing temperature is the obstacle in the fabrication of oxygen gas sensor. It is thus desirable to develop TiO2 thin film preparation technique that provides the anatase phase for oxygen gas sensor at low and short annealing temperature. In this study, the dip coating method was used to fabricate the TiO2 thin film. The parameters such as deposition layer, withdrawal speed of dip coating and annealing temperature were varied to optimize the properties of thin film. The optimum parameters are obtained from the I layer deposition film, IO mm/ min withdrawal speed of dip coating, and annealed the film at 400 °C in electrical furnace. Crystal structure studies showed that the optimized TiO2 thin film is anatase phase with tetragonal lattice structure and (101) plane is the dominant peak. Morphological studies indicated that the film is even and uniform in manner with grain size of 13.3 nm. The crystallite size obtained from HIGHSCORE software is 69.02 nm and calculated crystallite size using Scherrer's equation is 55.7 nm. The electrical studies showed that the film resistivity is 1.64 x I 0-3 n.cm. The gas sensor measurement revealed that the response and recovery time of TiO2 thin film sensor at room temperature is about 13.22 s and 2.67 s, respectively. Thus, proving that the potential to use the TiO2 thin film fabricated by dip coating as active layer in oxygen gas sensor.